Rancangan Tata Letak Penempatan Barang Menggunakan Metode Class Based Storage Berdasarkan Rasio Persediaan - . Basuki (JURNAL CITRA WIDYA EDUKASI, 2021)
This research discusses the layout design of the placement of goods using the Class Based Storage method based on the inventory ratio. Difficulties that arise in planning the warehouse layout depend on the volume of incoming goods, types of goods, demand patterns and types of material handling used. The purpose of this research is to design a warehouse layout based on existing data and information in order to facilitate the storage and retrieval of goods in the warehouse. This research was conducted at PT X, Bekasi in February 2021. The research variables used were: 1) the code of goods from the supplier; 2) the layout is designed to adhere to the block system; and 3) the location of placement of each item in the block location. The data analysis methods used were: 1) identifying suppliers; 2) identify packaging; 3) determine storage limits; 4) counting stock; 5) creating a pattern of inventory; 6) determine the maximum number of storage; 7) counting the number of lots for each package; and 8) describe the layout. The result showed that the appropriate layout method is class based storage method, where the allocation of goods placement or class division is adjusted based on the type of case and the ratio of the amount of inventory or usage. The appropriate storage method is with a block system, not a rack system.